Acquisition of Classifier Constructions in HKSL by Bimodal Bilingual Deaf Children of Hearing Parents - Tang, Gladys W. L.; Li, Jia (Frontiers in Psychology, 2018)
The current study focuses on the acquisition of classifier constructions in HKSL by a group of Deaf children of hearing parents, aided or implanted. These children have been mainstreamed together since kindergarten; but their learning environment supports dual language input in Cantonese and Hong Kong Sign Language (HKSL) on a daily basis. Classifier constructions were chosen because previous research suggested full mastery at a late age when compared with other verb types, due to their morphosyntactic complexity. Also, crosslinguistic comparison between HKSL and Cantonese reveals differences in verb morphology as well as word order of the structures under investigation. We predicted that verb root and word order were the two domains for crosslingusitic interaction to occur. At the general level, given the specific learning environment and dual input condition, we examined if these Deaf child learners could ultimately acquire classifier constructions. Fifteen Deaf children divided into four groups based on duration of exposure to HKSL participated in the study. Two Deaf children born to Deaf parents and three native HKSL signers served as controls. A picture description task was designed to elicit classifier constructions containing either a transitive, a locative existential or a motion directional predicate. The findings revealed Deaf children’s gradual convergence on the adult grammar despite late exposure to HKSL. Evidence of crosslinguistic influence on word order came from the Deaf children’s initial adoption of a Cantonese structure for locative existential and motion directional predicates. There was also a prolonged period of adherence to the SVO order across all grades. However, within this SVO structure, the verb revealed increasing morphological complexity as a function of longer duration of exposure. We interpreted the findings using Language Synthesis, arguing that it was the selection of morphosyntactic features in Numeration that triggered crosslinguistic interaction between Cantonese and HKSL with bimodal bilinguals.